2015
DOI: 10.1308/003588414x14055925059633
|View full text |Cite
|
Sign up to set email alerts
|

A review of cervical spine injury associated with maxillofacial trauma at a UK tertiary referral centre

Abstract: The presence of maxillofacial trauma mandates exclusion and prompt management of cervical spine injury, particularly in RTA and trauma cases involving combined facial fracture patterns. This approach will facilitate management of maxillofacial fractures within an optimum time period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 35 publications
7
28
4
1
Order By: Relevance
“…The findings of the study were similar to those of Mokerji et al [4]. In his study, fracture and dislocation of the cervical vertebrae was a total of 63 percent and disc herniation and spinal cord contusion were 37% among the patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of the study were similar to those of Mokerji et al [4]. In his study, fracture and dislocation of the cervical vertebrae was a total of 63 percent and disc herniation and spinal cord contusion were 37% among the patients.…”
Section: Discussionsupporting
confidence: 89%
“…Motorcycle riders are another high risk group in traffic accidents [2] [3]. Mokerjy et al [4] demonstrated in their study that from 714 patients with fractures, traffic accident was the cause of 88 percent of the fractures. Shazia [5] also indicated that in all cases of maxillofacial fractures, the cause was traffic accidents.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of C-spine injuries varies from 0% to 8% in maxillofacial injuries. Mukherjee et al [14] found that patients with mixed mandibular and nonmandibular fractures had a higher incidence of C-spine injuries than those with mandibular fracture only and nonmandibular fracture only, with the rates of 12.8%, 1.8%, and 1.5%, respectively [14]. Vital transportation, e.g.…”
Section: Associated Injuriesmentioning
confidence: 99%
“…In this research, craniofacial trauma affected one third of the victims of SCT. In the United Kingdom, it was found that the occurrence of spinal injury was significant among victims of maxillofacial trauma [56]. In addition, with regard to the etiology of the injury, the occurrence of spinal injuries in victims of oral and maxillofacial trauma resulting from traffic accidents was four times higher.…”
Section: Discussionmentioning
confidence: 99%